Inhaled nitric oxide for adults with pulmonary non-tuberculous mycobacterial infection. (January 2023) - Flume, Patrick A.; Garcia, Bryan A.; Wilson, Dulaney; Steed, Lisa; Dorman, Susan E.; Winthrop, Kevin
Abstract: Question: There is an increasing prevalence of nontuberculous mycobacteria pulmonary disease (NTM-PD) in the US. Treatment of NTM-PD typically requires multiple medications, which can be associated with unpleasant morbidity and eradication of infection is difficult. Therefore, there is a critical need for novel effective and well-tolerated therapies. Recent in vitro data and case reports have suggested that nitric oxide, inhaled as a gas (gNO), has antimicrobial activity against NTM. We sought to investigate the effect of gNO in patients with NTM-PD in an open-label proof of concept trial. Methods: Eligible participants had NTM-PD with persistently positive respiratory cultures for NTM even if on antibiotic treatment. Participants were treated with gNO for 50 min three times daily, five days per week, for three weeks (total of 15 treatment days). Results: Ten participants, of whom nine were on long-term NTM antibiotic therapy, were enrolled. All participants completed the regimen without interruption or discontinuation. Small increases in methemoglobin were noted during treatment, and all resolved to baseline within 2 h. Four participants (40%) met the primary outcome measure of negative sputum cultures after three weeks of therapy. Following treatment discontinuation, three of these participants were again culture positive during the 3-month post-treatment monitoring period, although with measures suggesting low bacterial burden. Answer: Patients tolerated a 3-week regimen of gNO without safety concerns, and despite highly refractory disease four individuals completed the study with negative cultures, although three were again positive in subsequent months. These data support further investigation of gNO as a potential therapy for NTM-PD.